ANALISIS TINGKAT KEPENTINGAN DAN KINERJA PELAYANAN KEDAI KOPI KETJE DAN LOKAL COFFEE DI KOTA METRO - Agus Hudoyo; Tri Tarsita Aprilyano (Universitas Galuh, 2022)
The increased number of coffee shops has led to increasingly fierce competition. A coffee shop needs to provide the best service so customers are satisfied if the performance of service attributes are considered important according to customer expectations. This study aimed to identify service attributes of coffee shops based on their importance and performance and analyze service attributes need to be maintained and improved their performance. There were two coffee shops studied, Kopi Ketje (KK) and Local Coffee (LC) were located in Metro City, Lampung Province. Data collection was carried out in August-September 2020. The number of samples for each shop was 35 respondents with total sample was 70 respondents. The sampling technique was carried out in stages. The day and time of interview was set intentionally. A sample was selected randomly based on table numbers. Attributes of importance and performance were measured on a likert scale using questionnaire. The questionnaire with 25 Attribute of importance and satisfaction has been valid and reliable. Data were analyzed using Importance Performance Analysis (IPA) method. The results showed there were 15 attributes in KK and 13 attributes in LC which considered important by respondents. The results of this study indicated 9 attributes in KK and 7 attributes in LC which are considered satisfactory. Attributes that need to be maintained were 9 attributes in KK and 7 attributes in LC. Performance attributes that need to be improved were 6 attributes in each shop.